Cover - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
A New Approach to Estimate the Potential Assets Loss due to Dam - Break Event in Indonesia Farrel Wiguna, Doddi Yudianto, Bobby Minola Ginting & Albert Wicaksono The Effect of Addition RAP as Quality Improved for Hot Paved Mixtures Irfan Zhain, Ria Asih Aryani Soemitro & Hitapriya Suprayitno The Socio-economic Transformations in the Peri-urban of Bandung Metropolitan Area Yanti Budiyantini & Sheilla Alviany The spatiotemporal variable effects of individuals' CO2 emission in Bandung Metropolitan Areas Dimas B.E. Dharmowijoyo & Cynthia D. Maharani Managing the Past into Future: Materiality and Discourse on Cultural LandscapeWijaya Martokusomo Wijaya Martokusumo